Nanobioconjugates for Signal Amplification in Electrochemical Biosensing - Sebastian Cajigas; Jahir Orozco (Molecules, 2020)
Nanobioconjugates are hybrid materials that result from the coalescence of biomolecules and nanomaterials. They have emerged as a strategy to amplify the signal response in the biosensor field with the potential to enhance the sensitivity and detection limits of analytical assays. This critical review collects a myriad of strategies for the development of nanobioconjugates based on the conjugation of proteins, antibodies, carbohydrates, and DNA/RNA with noble metals, quantum dots, carbon- and magnetic-based nanomaterials, polymers, and complexes. It first discusses nanobioconjugates assembly and characterization to focus on the strategies to amplify a biorecognition event in biosensing, including molecular-, enzymatic-, and electroactive complex-based approaches. It provides some examples, current challenges, and future perspectives of nanobioconjugates for the amplification of signals in electrochemical biosensing.